Witnessing the onset of reionization through Lyman-α emission at redshift 13 - Joris Witstok; Peter Jakobsen; Roberto Maiolino; Jakob M. Helton; Benjamin D. Johnson; Brant E. Robertson; Sandro Tacchella; Alex J. Cameron; Renske Smit; Andrew J. Bunker; Aayush Saxena; Fengwu Sun; et al. (Nature, 2025)
Abstract Cosmic reionization began when ultraviolet (UV) radiation produced in the first galaxies began illuminating the cold, neutral gas that filled the primordial Universe1,2. Recent James Webb Space Telescope (JWST) observations have shown that surprisingly UV-bright galaxies were in place beyond redshift z = 14, when the Universe was less than 300 Myr old3–5. Smooth turnovers of their UV continua have been interpreted as damping-wing absorption of Lyman-α (Ly-α), the principal hydrogen transition6–9. However, spectral signatures encoding crucial properties of these sources, such as their emergent radiation field, largely remain elusive. Here we report spectroscopy from the JWST Advanced Deep Extragalactic Survey (JADES10) of a galaxy at redshift z = 13.0 that reveals a singular, bright emission line unambiguously identified as Ly-α, as well as a smooth turnover. We observe an equivalent width of EWLy-α > 40 Å (rest frame), previously only seen at z < 9 where the intervening intergalactic medium becomes increasingly ionized11. Together with an extremely blue UV continuum, the unexpected Ly-α emission indicates that the galaxy is a prolific producer and leaker of ionizing photons. This suggests that massive, hot stars or an active galactic nucleus have created an early reionized region to prevent complete extinction of Ly-α, thus shedding new light on the nature of the earliest galaxies and the onset of reionization only 330 Myr after the Big Bang.